Pembuatan Website E-Commerce Penjualan Sepeda Listrik Menggunakan Metode User Centered Design - Abdullah Dzanuar Althaf mu'tasyim; Yusni Nyura; Damar Nurcahyono (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2026)
The rapid development of information technology has encouraged businesses to adopt e-commerce systems to improve sales efficiency and business performance. This study aims to develop an e-commerce website for electric bicycle sales using the User Centered Design (UCD) method, which focuses on user needs and experiences throughout the system development process. The UCD approach was implemented through several stages, including user requirement analysis, system design, implementation, testing, and usability evaluation. The system was developed using the Laravel framework and MySQL database, providing key features such as product management, shopping cart, checkout, online payment integration, inventory management, and sales reporting. Functional testing was conducted using the Black Box Testing method, and the results showed that all system features operated according to the specified requirements. Furthermore, usability evaluation was carried out using the System Usability Scale (SUS) involving 20 respondents. The evaluation produced an average SUS score of 83.25, which falls into the Excellent category, Grade A, and Acceptable range. These results indicate that the developed website is highly usable, easy to learn, and capable of supporting sales transactions effectively. Therefore, the implementation of the UCD method has proven effective in developing an e-commerce system that meets user expectations and supports the digital transformation of electric bicycle businesses.